2011
DOI: 10.1590/s0044-59672011000200019
|View full text |Cite
|
Sign up to set email alerts
|

LD5o of the bacteria Aeromonas hydrophila to matrinxã, Brycon amazonicus

Abstract: In order to determine the lethal dose (96-h LD 50 ) of the bacteria Aeromonas hydrophila to matrinxã, Brycon amazonicus, to be applied in challenge tests, 90 fish (63.23 ± 6.39 g) were divided into five treatments, with different bacterial solutions: T 1 -Control (0.9% NaCl saline solution); T 2 (4 x 10 11 cells/ mL); T 3 (5 x 10 11 cells/ mL); T 4 (1.36 x 10 12 cells/ mL) and T 5 (3.06 x 10 12 cells/ mL). Fish were previously anesthetized with benzocaine (60 mg L -1 ), inoculated in the peritoneal cavity with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…The abraded O. niloticus fries experienced significantly low moralities (37%) and high RPS (53.2) compared to abraded juveniles (90%) and low RPS (25.9) when challenged with A. hydrophila. It has been demonstrated that the effects of A. hydrophila infection in fish can vary according to the resistance to infection (Schlotfeldt and Alderman, 1995) and with the size of the animal (Oliveira et al, 2011). The present results corroborate the observations of Haque et al, (2014), who demonstrated the effectiveness of 2 g OTC/kg diet in reducing the bacterial load of fish under artificial culture condition.…”
Section: Efficacy Of Otc Therapiessupporting
confidence: 90%
“…The abraded O. niloticus fries experienced significantly low moralities (37%) and high RPS (53.2) compared to abraded juveniles (90%) and low RPS (25.9) when challenged with A. hydrophila. It has been demonstrated that the effects of A. hydrophila infection in fish can vary according to the resistance to infection (Schlotfeldt and Alderman, 1995) and with the size of the animal (Oliveira et al, 2011). The present results corroborate the observations of Haque et al, (2014), who demonstrated the effectiveness of 2 g OTC/kg diet in reducing the bacterial load of fish under artificial culture condition.…”
Section: Efficacy Of Otc Therapiessupporting
confidence: 90%
“…The lethal concentration of A. hydrophila for A. gigas, was 1.8 Â 10 8 CFU/mL, similar concentration to that described for Pangasius bocourti, 2.2 Â 10 8 CFU/mL (Doan, 2013). In contrast, it was lower when compared to reported lethal concentration for Brycon amazonicus, which was 6.6 Â 10 11 CFU/mL and early mortality occurred only after 57 h of the beginning of intraperitoneal cavity inoculation (Oliveira et al, 2011). Studies performed in Labeo rohita showed that concentrations of 2.2 Â 10 7 , 2.2 Â 10 8 and 2.2 Â 10 9 CFU/mL of A. hydrophila caused 100% mortality in 24 h after intraperitoneal inoculation, but early mortality occurred after 3 h from the beginning of the bacterial inoculation (Bharadwaj et al, 2013).…”
Section: Discussionmentioning
confidence: 55%
“…Before performing the bacteria challenge to the fish under study, the LD50 dose of the bacteria was established by challenging another group of fish to the unrelated but same bacteria species according to the method of Oliveira et al (2011). Ninety individuals were divided into nine tanks (=10 in each tank).…”
Section: Bacterial Pathogen and Experimental Challengementioning
confidence: 99%